2015
DOI: 10.1016/j.jgeb.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Cow dung is an ideal fermentation medium for amylase production in solid-state fermentation by Bacillus cereus

Abstract: Amylase production by Bacillus cereus IND4 was investigated by solid state fermentation (SSF) using cow dung substrate. The SSF conditions were optimized by using one-variable-at-a-time approach and two level full factorial design. Two level full factorial design demonstrated that moisture, pH, fructose, yeast extract and ammonium sulphate have significantly influenced enzyme production (p < 0.05). A central composite design was employed to investigate the optimum concentration of these variables affecting amy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 24 publications
(22 reference statements)
2
18
3
Order By: Relevance
“…Amylase concentration significantly changed with the initial pH values, and the maximum yield was found at pH 8.0 and activity decreased with increasing pH values. Amylase production from Bacillus cereus under solid-state fermentation was reported in alkaline pH [31]. In contrast to our results, Dar et al [29] obtained maximum amylase concentration in acidic pH (6.00) from Penicillium chrysogenum.…”
Section: Optimization Of Fermentation Conditions For Amylase Productioncontrasting
confidence: 99%
“…Amylase concentration significantly changed with the initial pH values, and the maximum yield was found at pH 8.0 and activity decreased with increasing pH values. Amylase production from Bacillus cereus under solid-state fermentation was reported in alkaline pH [31]. In contrast to our results, Dar et al [29] obtained maximum amylase concentration in acidic pH (6.00) from Penicillium chrysogenum.…”
Section: Optimization Of Fermentation Conditions For Amylase Productioncontrasting
confidence: 99%
“…The enzyme was found stable up to pH 6.0-10.0 for 4 h of incubation, indicating one of the most important characteristics of this isolate. The finding of this study showed superiority to the previous reports of Aygan et al (2008) and Vijayaraghavan et al (2015) who demonstrated the stability of crude amylase up to pH 9.0 and 8.0, respectively, from the respective isolates. The alkali-tolerant property of amylases from strain ALA4 for a longer period proved the isolate to be a potent source for varied biotechnological application, as suggested by Pal and Khanum (2010) too.…”
Section: Discussioncontrasting
confidence: 47%
“…The utilization of soluble starch for the production of reasonable amount of extracellular amylase was previously reported by Tiwari et al (2014) and Khusro and Aarti (2015). In contrary to this, Narang and Satyanarayana (2001), and Vijayaraghavan et al (2015) demonstrated the increased amylase yield in the presence of lactose and fructose, respectively, from respective bacterial sources. In the present investigation, among eight nitrogen sources tested, yeast extract (organic nitrogen source) depicted the maximum yield of extracellular amylase.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations